Gamma Radiation Effect on Growth, Production and Lignin Content of Sorghum sudanense at Different Harvest Ages - Maudi Nayanda Delastra; Andriyani Astuti; Bambang Suwignyo; Muhlisin Muhlisin; Nafiatul Umami (Buletin Peternakan, 2021)
The purpose of this study was to determine the effect of gamma-ray irradiation on Sorghum sudanense in the first offspring (F1) on plant growth, production, and lignin content at different harvest ages. This study used a split-plot design in which varieties of Sorghum sudanense with gamma irradiation and Sorghum sudanense without gamma irradiation are the main plot. Meanwhile, the harvest age is the subplot. The planting area was 1.5x1.5 m, each with 3 replications. The materials used were Sorghum sudanense without gamma-ray irradiation and the first generation seeds (F1) of Sorghum sudanense with gamma irradiation. The method used was irradiating Sorghum sudanense seeds with gamma-ray with a dose of 300 Gy, planting, maintenance, and harvesting. The harvest ages were 50, 70, and 90 days. The data observed were plant growth, namely plant height and length, dry matter (DM) and organic matter (OM) production, and lignin content. Sorghum sudanense with gamma irradiation had higher plant height, plant length, also DM, and OM production (P<0.05) than Sorghum sudanense without gamma irradiation. The lignin content of Sorghum sudanense with gamma irradiation was lower (P<0.05) than Sorghum sudanense without gamma irradiation. Longer harvest age increased (P<0.05) plant height, plant length, production, and lignin content. In conclusion, there were characteristics differences between Sorghum sudanense with gamma irradiation and without gamma irradiation (parents). The longer harvest led to higher plant height, length, production, and lignin content. There was an interaction (P<0.05) between varieties and harvest ages. Gamma irradiated Sorghum sudanense had a peak production at the age of 70 days, with a lignin content of 3.63%.